The Influence of High-Performance Work Systems and‎Organizational Culture and Employee Performance Mediated by ‎Abilities, Motivation, and Career Opportunities in The Kendari City ‎Government - Yuana , Indira; Madjid, Rahmad; Rosnawintang; Adam, La Ode Bahana (International Journal of Accounting and Economics Studies, 2025)
The population was ‎329 people on the State Civil Apparatus of Kendari City Government Regional Services and Agencies, using the ‎Proportionate Stratified Random Sampling technique. Research variable data were analyzed using structural equation modeling (SEM) with ‎the AMOS program. The research results show that: (1) a high-performance work system has a positive and significant effect on ability, ‎motivation and career opportunities, but the positive effect is not significant on employee performance; (2) organizational culture has a positive ‎and significant effect on abilities and career opportunities, but the positive effect is not significant on employee motivation and performance; ‎‎(3) ability and career opportunities influence employee performance, but motivation does not significantly influence employee performance; ‎‎(4) high-performance work systems influence employee performance mediated by ability and career opportunities, but motivation does not ‎mediate the influence of high-performance work systems on employee performance; (5) organizational culture influences employee ‎performance mediated by abilities and career opportunities, but motivation does not mediate the influence of organizational culture on ‎employee performance.